SUITABILITY OF SPATIAL-TEMPORAL HABITAT OF YELLOWFIN TUNA (Thunnus albacares) USING MAXIMUM ENTROPY MODEL IN WEST SUMATRA - Noferdiman; Heltria, Septy; Endang G, Ester Restiana; Ramdhani, Farhan; Yuliardi, Amir Yarkhasy (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2024)
Yellowfin tuna is one of the main catches in West Sumatera waters and has a high economic value. Fishing optimization can be improved through spatial and temporal predictions of fishing areas for effective fisheries management. This research aims to predict fishing areas using an oceanographic data approach through maximum entropy (MaxEnt) modelling. Data collection incorporating sea surface temperature and chlorophyll-a were obtained from the Aqua-Modis satellite in 2022 as well as fishing point data from Ocean Fishing Port (OFP) Bungus. The MaxEnt model shows a good level of accuracy in the West season (AUC 0,860), 1st Transitional season (AUC 0,918), East season (AUC 0,918), and 2nd Transitional season (0,920) The contribution of chlorophyll for one year is more significant, accounted for 75,3%, compared to sea surface temperature, constituted 24,7%. The Sea Surface Temperature (SST) values in West Sumatera waters vary on each season, ranging from 26,4 to 34.5 ℃ and the chlorophyll-a fluctuate between 0,03 and 5,45 mg/m3. The distribution of yellowfin tuna habitat on the map shows that most fishing vessel coordinates are in the Habitat Suitability Index (HSI) HSI value of 0,6 – 0,9. Potential areas for catching yellowfin tuna are around the Mentawai Islands. Keywords: Chlorophyll-a, HSI, Maximum Entropy Model, Sea Surface Temperature, Yellowfin Tuna